Gundi (Cordia gharaf): An Un-tapped Arid Fruit for Commercial Promotion - Kumawat, K L; Gurjar, P S; Samadia, D K; Sarolia, D K (Indian Horticulture, 2025)
Gundi (Cordia gharaf) is a highly valuable arid-zone fruit species. Despite its immense potential as a source of high-quality fruits for rural income and as fodder for livestock nutrition, it remains largely underexploited. This multipurpose species thrives during peak of the summer, bearing fruits and lush green foliage even under the harsh environmental conditions of arid and semi-arid regions. The gundi tree has a deep and robust taproot system and exhibits several adaptive traits such as waxy leaves, dense hairiness, and remarkable tolerance to salinity, extreme heat, and prolonged drought. These traits not only enhance its resilience to climate stressors but also establish its vital role in dryland ecosystems. Given its multiple benefits, gundi has emerged as a promising candidate for domestication and commercial cultivation, particularly in water-scarce and degraded landscapes. Despite its utility, this species has received limited research attention. In response, ICAR-CIAH, Bikaner, has initiated efforts for its horticultural development and genetic conservation. Significant gaps remain in areas such as genetic variability utilization, varietal orchard development, production models, and value-added product commercialization. Advancing scientific research on gundi could unlock new socio-economic and environmental opportunities.